Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja terhadap Kepuasan Kerja Karyawan - Nurdin Nurdin; Tjipto Djuhartono (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
This study aims to determine the magnitude of the influence of leadership style and work environment on employee job satisfaction. The research method is a survey research. The subjects of this research are 30 employees in the city of Bekasi. The data were collected by means of a questionnaire using a Likert instrument. The validity of the data was obtained by testing the validity and reliability, all data had a normal distribution. The results showed that leadership style had a significant influence on employee job satisfaction. Likewise, the work environment has a significant influence on employee job satisfaction. The coefficient of determination (R)2 is that leadership style and work environment have a strong influence on employee job satisfaction. Keywords: Job Satisfaction, Leadership, Environment